PIDATO PANCASILA 1 JUNI 1945 SOEKARNO PERSPEKTIF ORDINARY LANGUAGE PHILOSOPHY - Zainal Fadri (Sekolah Tingi Keguruan dan Ilmu Pendidikan (STKIP) PGRI Tulungagung, 2020)
This study aims to answer questions regarding the concept of Soekarno's speech on June 1, 1945. The speech that was delivered at that time was then analyzed using the ordinary language approach. The method used in this research is descriptive qualitative. Research data is obtained from searching the literature from books, journals and related articles in order to get a comprehensive and in-depth idea or idea. The results of this study indicate that Soekarno's speech on June 1 revealed the attitudes and statements in the statement that contained every sentence that was conveyed, so that re-interpreting the text is an activity that must be carried out by the next generation.Keywords: Soekarno's speech, ordinary language, JL. Austin